2009
DOI: 10.1111/j.1751-1097.2008.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Photodynamic Eradication of Pseudomonas aeruginosa in Planktonic and Biofilm Culture

Abstract: Photodynamic disinfection (PDD) is a nonantibiotic approach to treating drug-resistant bacterial infections. Pseudomonas aeruginosa, an opportunistic pathogen, is problematic because of its propensity to develop antibiotic resistance and its ability to secrete a protective biofilm matrix. This study examined the ability of PDD to eradicate planktonic and biofilm cultures of P. aeruginosa in vitro. Planktonic P. aeruginosa cultures were briefly exposed to a methylene blue-based photosensitizer formulation and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 35 publications
(43 reference statements)
2
27
1
Order By: Relevance
“…Based on the coloring conditions after culture, bacterial identification results could be accurately obtained in a short time period. Patients who had bacterial culture results that were positive for PA after 3 days and who met the inclusion criteria were included in the study [27].…”
Section: Bacterial Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the coloring conditions after culture, bacterial identification results could be accurately obtained in a short time period. Patients who had bacterial culture results that were positive for PA after 3 days and who met the inclusion criteria were included in the study [27].…”
Section: Bacterial Identificationmentioning
confidence: 99%
“…However, the specific mechanism for this action requires further elucidation. Additionally, Street et al [27]. demonstrated that methylene blue-based PDT at a dose [15.5 J/cm 2 could completely eradicate planktonic PA and inhibit biofilms at a rate of 99 %.…”
Section: Introductionmentioning
confidence: 97%
“…Development of bacterial resistance has not yet been shown and could not be generated in an experimental study protocol [14]. aPDT was shown to be able to eliminate the specific periodontopathogenic bacterium Aggregatibacter actinomycetemcomitans in a planktonic biofilm model [15], and to effectively eradicate planktonic and biofilm cultures of the opportunistic pathogen Pseudomonas aeruginosa [16]. Moreover, multispecies microbial biofilms and suspensions of microorganisms were developed from dental plaque samples and treated photodynamically.…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for this variability, while likely in part due to small sample sizes of studies published to date, can be theorized from preclinical studies that preceded this clinical work. As demonstrated in several preclinical aPDT studies, 51,97,98 the importance of delivering an optimal activating light energy dose cannot be understated. While it is difficult to pinpoint a precise power density or energy dose threshold for clinical use using preclinical results, it is clear that antibacterial efficacy drops off dramatically when insufficient light is delivered to the site of treatment.…”
Section: Human Clinical Applications For Oral Apdtmentioning
confidence: 97%